Persistent Left SVC Draining to Right Atrium through Common Channel with Suprahepatic IVC: A Rare Finding - Bhardwaj, Akshit; Kushwaha, Dinesh Singh; Prabhakar, Ankit; Sharma, Pankaj (Journal of Clinical Interventional Radiology ISVIR, 2024)
The knowledge of different anatomic venous variants of central vessels is essential to improve the safety of procedures like central venous access and tunneled central catheter (TCC) placement. Persistent left superior vena cava (PLSVC) is an uncommon variant seen in 0.5 to 2% of common population, in 80 to 90% of which PLSVC commonly drains into the right atrium (RA) via the coronary sinus. We describe a rare case of PLSVC draining into RA through common channel with suprahepatic inferior vena cava, encountered while placing TCC into left internal jugular vein. This report highlights the radiological findings and the implications of this anatomic anomaly.
Keywords: congenital abnormality; tunneled central catheter; persistent left superior vena cava